Comparison of theoretical denaturation maps of phiX174 and SV40 with their gene maps. - Tong, B Y (1979)
When the theoretical denaturation maps of phiX174 and SV40 are compared with their gene maps, it is observed that the beginning and the end of each gene in these two DNA's fall in a region of lower melting temperatures. Local (A+T)-contents evaluated from the known sequences at these regions support the above implication that the beginnings and the ends of nearly all the genes in phiX174 and SV40 are relatively rich in (A+T)-content.